Integrating a Photocatalyst into a Hybrid Lithium–Sulfur Battery for Direct Storage of Solar Energy1. (10th June 2015) - Li, Na; Wang, Yarong; Tang, Daiming; Zhou, Haoshen
Abstract Direct capture and storage of abundant but intermittent solar energy in electrical energy‐storage devices such as rechargeable lithium batteries is of great importance, and could provide a promising solution to the challenges of energy shortage and environment pollution. Here we report a new prototype of a solar‐driven chargeable lithium–sulfur (Li‐S) battery, in which the capture and storage of solar energy was realized by oxidizing S2− ions to polysulfide ions in aqueous solution with a Pt‐modified CdS photocatalyst. The battery can deliver a specific capacity of 792 mAh g−1 during 2 h photocharging process with a discharge potential of around 2.53 V versus Li+/Li. A specific capacity of 199 mAh g−1, reaching the level of conventional lithium‐ion batteries, can be achieved within 10 min photocharging. Moreover, the charging process of the battery can proceed under natural sunlight irradiation.